2008
DOI: 10.1002/aoc.1386
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substituents in the salicylaldehyde‐derived Schiff bases on vanadium‐catalyzed asymmetric oxidation of sulfides

Abstract: A series of chiral Schiff bases (L 1 -L 5 ) with different substituents in the salicylidenyl unit were prepared from condensation of 3-aryl-5-tert-butylsalicylaldehyde derivatives and optically active amino alcohols. Bromination of 3-phenyl-5-tertbutylsalicylaldehyde gave an unexpected product 3-(4-bromophenyl)-5-bromosalicylaldehyde, from which the corresponding Schiff base ligands L 6 and L 7 , derived from (S)-valinol and (S)-tert-leucinol, respectively, were prepared. Ligands L 1 -L 7 were applied to the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…, Liu et al 80 and Li et al 82 also found dichloromethane, and chloroform to be superior to other solvents for this oxidation, confirming Ellman's results. 89 This gave superior enantioselectivity (98% ee) compared to dichloromethane (90% ee), however, the yield obtained (61%) was lower than when using dichloromethane (75%).…”
supporting
confidence: 71%
“…, Liu et al 80 and Li et al 82 also found dichloromethane, and chloroform to be superior to other solvents for this oxidation, confirming Ellman's results. 89 This gave superior enantioselectivity (98% ee) compared to dichloromethane (90% ee), however, the yield obtained (61%) was lower than when using dichloromethane (75%).…”
supporting
confidence: 71%
“…Sun and co-workers examined a series of 3-aryl-substituted chiral ligands of the type 105 in vanadium-catalyzed oxidations of aryl methyl sulfides, and reported moderate to good enantioselectivities (53–92% ee). , tert -Leucinol-derived ligands were shown to afford better asymmetric induction than valine- or phenylalanine-derived structures. The catalyst system VO­(acac) 2 / 106 exhibited enantioselectivities up to 77% ee in oxidation of aryl methyl sulfides in acetone …”
Section: Asymmetric Sulfoxidation Reactionsmentioning
confidence: 99%
“…In the vanadium catalyzed sulfoxidation reaction, halo‐substituted salicylaldehyde Schiff base exhibited excellent chiral induction, therefore, we synthesized and applied dibromo‐, diiodo‐, and ortho ‐bromo substituted ligands 31 (SBAIB‐8), 32 (SBAIB‐9) and 33 (SBAIB‐10) for this reaction; all ligands produced moderate enantioselectivity (entries 8—10, Table ,). In addition, extremely sterically hindered phenyl substituted ligands 34 (SBAIB‐11) and 35 (SBAIB‐12) were screened; they exhibited only moderate chiral induction (58 and 68 % ee ) for this reaction.…”
Section: Resultsmentioning
confidence: 99%